2009
DOI: 10.4161/cbt.8.15.9133
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing immune responses to tumor-associated antigens

Abstract: The goal of vaccine-based cancer immunotherapy is to induce a tumor-specific immune response that ultimately reduces tumor burden. However, the immune system is often tolerant to antigens presented by the tumor, as the cancer originates from within a patient and is therefore recognized as self. This article reviews selected clinical strategies for overcoming this immune tolerance, and approaches to enhance generation of immunity to tumor-associated antigens by activating innate immunity, potentiating adaptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 120 publications
(133 reference statements)
0
47
0
1
Order By: Relevance
“…126,127 The simplicity of cryoablation coupled with its minimal negative effects on the immune system make this procedure an attractive candidate for combination regiment with immunotherapy. 124 Chemotherapy Long-standing dogma suggested that myelosuppressive effects of chemotherapy would prevent its application in combination with immunotherapy. However, this assumption was challenged by a large amount of experimental data obtained in recent years.…”
Section: Cryoablationmentioning
confidence: 99%
See 1 more Smart Citation
“…126,127 The simplicity of cryoablation coupled with its minimal negative effects on the immune system make this procedure an attractive candidate for combination regiment with immunotherapy. 124 Chemotherapy Long-standing dogma suggested that myelosuppressive effects of chemotherapy would prevent its application in combination with immunotherapy. However, this assumption was challenged by a large amount of experimental data obtained in recent years.…”
Section: Cryoablationmentioning
confidence: 99%
“…Recent data indicates that RFA enhanced DC maturation, increased the frequency of tumor-specific T-cells, and reduced Treg numbers, making RFA plus immunotherapy an appealing combination approach for cancer therapy. 123,124 High-intensity focused ultrasound (HIFU) is a technique in which a transducer is used to generate high-frequency ultrasound waves focused on a single point in the tumor. HIFU can deliver a large amount of energy that is subsequently converted to thermal energy, resulting in tumor cell destruction with minimal damage to the surrounding tissue.…”
Section: Physical Treatmentsmentioning
confidence: 99%
“…1): the cellular and molecular features of this biological scenario can ultimately tip the balance towards an effective immune response rather than immunological tolerance or even ignorance [99][100][101][102]. Based on this general concept, a variety of strategies have been devised to polarize the immune system against cancer: a comprehensive review of this ever growing field of research is beyond the scope of this article, and in this regard the readers are referred to dedicated review articles [103][104][105][106][107][108][109][110].…”
Section: Beyond Peptide Designmentioning
confidence: 97%
“…zielgerichteten (targeted) Therapieansätzen. Dabei verfügen konventionelle Krebstherapien wie die Chemotherapie oder Radiotherapie ihrerseits über Wirkmechanismen, die zur Potenzierung der antitumoralen Immunantwort beitragen können [26,27]. Beispielsweise kann ionisierende Strahlung eine vermehrte Expression von Zelloberflächenproteinen wie z.B.…”
Section: Pd-1-pathway Im Fokus - Weitere Potenziale Der Immunonkologiunclassified